2023
DOI: 10.29333/iji.2023.16149a
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Online Peer Feedback on Students’ Writing Skills during Corona Virus Pandemic

Abstract: The purpose of this study is to compare the impacts of two different modes of epeer feedback on the students' writing skills to see which mode should be better used to train the students' writing skills. The current study included 66 first-year students from the University of Foreign Language Studies in Danang City, Vietnam. The quasi-experimental research design was employed in the study. The two groups were taught how to compose a paragraph writing with peer comments in two rounds (1st & 2nd drafts). One gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
3
1
0
1
Order By: Relevance
“…This in return, helped them to read, edit and provide feedback to their peer's writings before their documents being finally evaluated by the teacher. This is consistent with Hamidun et al (2012), Rababah et al (2023), Tran(2023) who confirmed the importance of using constructive feedback in developing EFL writing skill.…”
Section: Discussion and Interpretation Of The Resultssupporting
confidence: 87%
“…This in return, helped them to read, edit and provide feedback to their peer's writings before their documents being finally evaluated by the teacher. This is consistent with Hamidun et al (2012), Rababah et al (2023), Tran(2023) who confirmed the importance of using constructive feedback in developing EFL writing skill.…”
Section: Discussion and Interpretation Of The Resultssupporting
confidence: 87%
“…The results of the current study confirm the view held by many researchers (Berg, 1999; Liu & Hansen, 2002; Pham & Nguyen, 2020; Pham et al, 2022; Tran & Pham, 2023) that students, particularly those who have received training in peer comments, are able to give useful comments in their peers’ drafts. Vo (2022) found the students were hppy to welcome both peer and teacher feedback.…”
Section: Discussionsupporting
confidence: 89%
“…It reflected how exposure to AW, teachers' and peers' comments and ideas helped students develop their AW significantly. It resonates with the findings of a Vietnamese quasi-experimental study (Tran & Pham, 2023) which reported that peer feedback has a significant influence on improving students' writing abilities. The students demonstrated an improvement in their ability to organize their ideas, use appropriate language, and provide proper citations and references in their seminar reports.…”
Section: Discussion and Feedback For Developing Writing Confidencesupporting
confidence: 84%